المساءلة النقدية لقيمة التراث العربي عند زكي نجيب محمود - علاء الدين, غسان; كحيلة, غياث (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research represents a try to show the direct and indirect reasons which made the contemporary Arab thinker Zaki Najeeb Mahmoud to change his opinion from the adoption of a frank speech about refusing Arab heritage and following the developed science of the west instead, to adoption of a confused speech about accepting what he had called the reasonable part of heritage, and trying to merge it with members of west civilization, in order to be Arab and contemporary Arab at the same time, by trying to introduce a clarification show which criticize the nature of these two opinions, that both represented a different phase in Mahmoud 's thinking schemeيمثل هذا البحث محاولة للوقوف على الأسباب الصريحة والمضمرة التي دفعت المفكر العربي المعاصر زكي نجيب محمود للتحول من موقف كان قد تبنى فيه خطاباً صريحاً نص على رفض التراث العربي والأخذ بعلم الغرب المتقدم كنموذج بديل، إلى موقف ذي خطاب ملتبس دعا فيه إلى قبول ما سماه بالجانب المعقول من التراث، ومحاولة دمجه مع عناصر الحضارة الغربية لنكون عرباً ومعاصرين في آن معاً، وذلك من خلال تقديم عرض توضيحي ذي طابع نقدي لطبيعة هذين الموقفين الذي مثل كل منهما مرحلة مختلفة عن الأخرى في مسيرة محمود الفكرية.